Development of pistachio spread using different formulations. - Shakerardekani, Ahmad; Karim, Roselina; Mohd Ghazali, Hasanah; Chin , Nyuk Ling (2012)
The pistachio nut (Pistacia vera L.) is a nutritious and popular tree nut that is consumed both as a roasted and salted nut. Non-split pistachios are used for the production of other products such as wafer, ice cream, chocolate, halvah, butter and spread. In this study, 17 pistachio spreads were formulated using various levels of pistachio paste, icing sugar, isolated soy protein and palm oil. The textural and rheological properties of pistachio spreads were measured using texture analyser and rheostress, respectively. Sensory acceptance of the products was carried out using Hedonic test. Significant correlation (r = -0.860, P˂ 0.05) were observed between sensory attributes (spreadability, overall texture and overall acceptability) and work of shear. The results showed that the presence of palm oil has a direct effect on both the elastic and viscous behaviour of the pistachio spread. Formulation 12 (50% pistachio paste, 30% sugar, 20% palm oil) and 16 (58.3% pistachio paste, 25% sugar, and 16.7% palm oil) were found to be acceptable in terms of sensory attributes, textural and rheological properties.